Characteristics of cell growth and lipid accumulation of high and low lipid-producing strains of Mucor circinelloides grown on different glucose-oil mixed media. (September 2018) - Zan, Xinyi; Tang, Xin; Chu, Linfang; Song, Yuanda
Graphical abstract: Highlights: The highest biomass of 21.2 g/L and the highest lipid content of 65% were obtained for M . circinellodes . M . circinelloides preferred to assimilate exogenous PA, SA and ALA. Soybean phospholipids and phytosterol esters more efficiently stimulated the production of intracellular lipases than soybean oil in M . circinelloides . The maximum intracellular lipase activity is up to 2200 U/g protein in CBS 277.49. Abstract: Mucor circinelloides is one of the few oleaginous fungi that produce large amounts of γ-linolenic acid (GLA). However, there are few reports regarding the lipid accumulation characteristics and assimilation preferences of M. circinelloides grown on different oils. The present study investigated the characteristics of cell growth, lipid accumulation, and lipase activity of a low lipid-producing strain M. circinelloides CBS 277.49 and a high lipid-producing strain M. circinelloides WJ11. The highest biomass of 21.2 g/L was obtained for CBS 277.49 grown on soybean oil, while the highest lipid content of 65% was obtained when WJ11 was grown on soybean phospholipids. M. circinelloides preferred to assimilate exogenous palmitic, stearic, and α-linolenic acid to synthesize intracellular triacylglycerols. Soybean phospholipids and phytosterol esters stimulated the production of intracellular lipases in both strains more efficiently than soybean oils. The maximal lipase activity of 2200 U/g protein was observed for CBS 277.49 grown on phytosterol esters, while the maximal lipase activity of 2000 U/g protein was observed for WJ11 grown on soybean phospholipids. Although the transcriptional levels of the lipase genes were sharply upregulated when strains were grown on glucose-oil mixed media, the extracellular lipase activity in the medium was still low at 4–210 U/g protein.